Aberrant RNA sensing in regulatory T cells causes systemic autoimmunity - Luca, Domnica; Lee, Sumin; Hirota, Keiji; Okabe, Yasutaka; Uehori, Junji; Izawa, Kazushi; Lanz, Anna-Lisa; Schütte, Verena; Sivri, Burcu; Tsukamoto, Yuta; Hauck, Fabian; Behrendt, Rayk; et al. (Science advances, 2024)
Chronic and aberrant nucleic acid sensing causes type I IFN-driven autoimmune diseases, designated type I interferonopathies. We found a significant reduction of regulatory T cells (Tregs) in patients with type I interferonopathies caused by mutations in ADAR1 or IFIH1 (encoding MDA5). We analyzed the underlying mechanisms using murine models and found that Treg-specific deletion of Adar1 caused peripheral Treg loss and scurfy-like lethal autoimmune disorders. Similarly, knock-in mice with Treg-specific expression of an MDA5 gain-of-function mutant caused apoptosis of peripheral Tregs and severe autoimmunity. Moreover, the impact of ADAR1 deficiency on Tregs is multifaceted, involving both MDA5 and PKR sensing. Together, our results highlight the dysregulation of Treg homeostasis by intrinsic aberrant RNA sensing as a potential determinant for type I interferonopathies.